Incorporation of philosophical ideas in science fiction literature - Tsvetkova, Milena; Arutyunyan, Margarita; Saenko, Natalya; Shramko, Ludmila; Kalimullin, Dilovar (Opción, 2019)
The study aims to investigate the incorporation of philosophical ideas in science fiction literature. The study used the methodology of quantitative research to collect and analyze interpretations and values of the survey. As a result, one of the most common philosophical ideas that can be found in science fiction is the speculation on the freedom of choice. In conclusion, the theme of the butterfly effect can be considered quite frequent, considering the interrelation of actions and their consequences.